(untitled) (Economic and Political Thought, 2017)
In order to be competitive in the market, a company must fight not only for customers but also for the best employees available in the market who can ensure adequate competitive advantage. To attract and retain such employees, a company must provide them with high remuneration and a wide range of fringe benefits. These incentives, however, are expensive and do not guarantee that employees will not leave to join a competitive company, which will offer them better conditions of employment. For this reason, companies are looking for new incentive systems that will retain the best employees in a given company. Such opportunities are provided by Long-Term Incentive Plans (LTIPs). Such plans are advantageous enough and it seems natural to use them in companies. The aim of this paper is to demonstrate the application of LTIPs in Polish public companies. To that end, the WIG20 companies have been used. The paper also examines the extent to which LTIPs are offered to members of the supervisory boards, measured by the share of their LTIP benefits in their total remuneration.